The effect of preharvest applications with biostimulants on qualitative properties and postharvest performance of loquat fruit - Pavlou, Andrea; Efstathiou, E.; Christodoulou, S. E.; Stylianou, S.; Manganaris, George A. (My University, 2022)
Loquat (Eriobotrya japonica L.) cultivation is one of the most promising crops under sub-tropical areas of the Mediterranean basin due to the fact that fruit ripening occurs in a period when there is no competition from other fresh fruits. The present work studied the effect of commercial formulations of biostimulants on qualitative attributes and postharvest performance of loquat fruit. Fifteen trees of ‘Karantoki’ with similar vigour from a commercial orchard were segregated into five groups of three trees and received the following treatments: 1) control, 2) kelp, 3) Folicist, 4) Fylloton, and 5) a combination of Kriss and Sunred formulations at the dosages recommended by the manufacturers. The fruits of each group were harvested on three consecutive dates (H1, H2 and H3) and analyzed after maintenance at room temperature (shelf life) for 1 and 5 days, respectively. Notably, kelp formulation led to a significant advancement of on-tree ripening that is a desirable feature due to the higher prices the fruit receives on the market as an “off-season” product, as well as to a significant increment on fruit size. Furthermore, kelp- and Folicist-treated fruits were characterized by higher firmness retention and reduced weight loss compared to the rest treatments after shelf life periods. No beneficial effect was registered when Fylloton, Kriss and Sunred formulations were applied. The incorporation of biostimulants to the spray program of loquat trees need to be further dissected and accompanied by a cost/benefit analysis.
Keywords: Eriobotrya japonica; Sugars; Acids; Developmental stages; Biostimulants; Yield efficiency